Effect of baseline serum albumin concentration on outcome of resuscitation with albumin or saline in patients in intensive care units: analysis of data from the saline versus albumin fluid evaluation (SAFE) study - Study Investigators, SAFE (BMJ Publishing Group Ltd., 2006)
Objective To determine whether outcomes of resuscitation with albumin or saline in the intensive care unit depend on patients' baseline serum albumin concentration. Design Analysis of data from a double blind, randomised controlled trial. Setting Intensive care units of 16 hospitals in Australia and New Zealand. Participants 6045 participants in the saline versus albumin fluid evaluation (SAFE) study. Interventions Fluid resuscitation with 4% albumin or saline in patients with a baseline serum albumin concentration of 25 g/l or less or more than 25 g/l. Main outcome measures Primary outcome was all cause mortality at 28 days. Secondary outcomes were length of stay in the intensive care unit, length of stay in hospital, duration of renal replacement therapy, and duration of mechanical ventilation. Main results The odds ratios for death for albumin compared with saline for patients with a baseline serum albumin concentration of 25 g/l or less and more than 25 g/l were 0.87 and 1.09, respectively (ratio of odds ratios 0.80, 95% confidence interval 0.63 to 1.02); P=0.08 for heterogeneity. No significant interaction was found between baseline serum albumin concentration as a continuous variable and the effect of albumin and saline on mortality. No consistent interaction was found between baseline serum albumin concentration and treatment effects on length of stay in the intensive care unit, length of hospital stay, duration of renal replacement therapy, or duration of mechanical ventilation. Conclusion The outcomes of resuscitation with albumin and saline are similar irrespective of patients' baseline serum albumin concentration. Trial registration ISRCTN76588266.